The effect of sowing quantity and row spacing on seed production of few minor grass species - Martyniak, Danuta; Żurek, Grzegorz (Plant Breeding and Seed Science, 2012)
A wide range of seed material from different grass species is necessary to keep high quality grasslands and to create buffer zones between arable lands and forest and to recultivate waste or fallow land. Therefore, the aim of our research was to describe elements of seed propagation of some minor grass species. On the basis of field experiments, different spacing and seed quantities were investigated for Beckmannia eruciformis, Cynosurus cristatus and Elytrigia elongata aiming at an optimal seed production. Satisfying seed yields were obtained even at a reduced (50% to 75%) amount of seed quantity, as compared to theoretical (or normal) values, calculated on the basis of number of plants per area unit.